Psychological distress and loneliness among European university students during the COVID-19 pandemic: a European survey - Tian, Caixin; Abeldaño Zuñiga; Roberto Ariel; Foláyan, Moréniké Oluwátóyìn; Tuominen, Jarno; Virtanen, Jorma I. (Springer Science and Business Media LLC, 2026)
Background: The COVID-19 pandemic and various consequent isolation, quarantine and curfew measures to curb the spread of the virus caused an increase in anxiety, depression, and loneliness among university students. The aim of this study was to assess the association between psychological distress and loneliness among university students in Europe during the COVID-19 pandemic.
Methods: This cross-sectional study was part of the COVIDiSTRESS global survey conducted during the first wave of COVID-19 pandemic in 2020. We evaluated for psychological stress and loneliness among university students in Europe (n = 11 231) using the Perceived Stress Scale (PSS-10) and the Loneliness Scale (SLON-3). The associations between the students' psychological stress levels, loneliness, and perceived helplessness were analysed using chi-square test, ANOVA, t-test, and regression models.
Results: In total, 9737 university students (69.9% female) between 18 and 34 years (mean: 25.3 years from 13 European countries were included in the analyses. Most (89.6%) of the university students experienced moderate stress levels, with women reporting significantly more stress than men (p < 0.001). Differences in stress levels were also associated with geographic region, marital status, and age. Higher levels of psychological stress were associated with the students' loneliness levels; loneliness accounted for 12.9% of the variance in stress. Perceived helplessness was associated with loneliness and gender and country of residence.
Conclusions: Majority of the university students in Europe experienced increased level of stress and loneliness during the first wave of COVID-19. Perceived helplessness was significantly associated with stress and correlated with gender, various loneliness factors and country of origin.